THE INFLUENCE OF SOCIAL MEDIA PLATFORMS ON LANGUAGE DEVELOPMENT - Rabbimov Oybek Anvar ugli (International Journal of Literature and Language Studies, 2026)
Social media platforms play a significant role in shaping modern communication and language skills. This study investigates how social media usage affects vocabulary acquisition, writing, reading, and speaking abilities. Findings indicate that active engagement on social media can enhance informal language skills, improve vocabulary, and support intercultural communication. However, over-reliance on informal language may negatively influence academic writing and grammatical accuracy.